Bank competition and financial stability in the United Kingdom banking sector - Li, Zhiyu (2020)
This paper evaluates the impacts of bank competition on financial stability in the United Kingdom banking sector during the period between 2008 and 2019. Bank non-performing loan ratio, the Z-score and bank capitalization ratio are used to measure financial stability, while the Lerner index, the Herfindahl- Hirschman index on deposits and the Herfindahl- Hirschman index on loans are employed as the proxies of bank competition. The empirical results are in line with Competition-Stability theory, where a higher level of bank competition results in less overall bank risk and a higher capitalization level. In addition, the results also show that more competition is associated with riskier loans. In the meanwhile, competition is also associated with higher level of capitalization and ultimately reduced overall bank risk, this provides support for the traditional Competition-fragility theory. Overall, this paper provides support for the Competition-Stability theory.